PD-1/PD-L1 immune-checkpoint blockade induces immune effector cell modulation in metastatic non-small cell lung cancer patients: A single-cell flow cytometry approach - Fameli, Antonella; Nardone, Valerio; Shekarkar Azgomi, Mojtaba; Bianco, Giovanna; Gandolfo, Claudia; Oliva, Bianca Maria; Monoriti, Marika; Saladino, Rita Emilena; Falzea, Antonella; Romeo, Caterina; Calandruccio, Natale Daniele; Azzarello, Domenico; et al. (Frontiers in Oncology, 2022)
PD-1/PDL1-immunecheckpoint blockade with mAbs to PD-1 (nivolumab or pembrolizumab) or PDL-1 (atezolizumab, durvalumab, or avelumab) alone or in combination with doublet chemotherapy, represents an expanding treatment strategy for metastatic NSCLC patients. This strategy lays on the capability of these mAbs of rescuing cytotoxic-T-cells inactivated by PD-1 engagement with PD-L1/2 within the tumor along the long lasting cancerogenesis process. This inhibitory interactive pathway is a physiological host mechanism aimed to prevent dangerous over-reactions and autoimmunity in case of prolonged and/or repeated CTL-response to the same antigen peptides. We have carried out a retrospective analysis to evaluate the ability of PD-1/PD-L1 blocking mAbs to trigger autoimmunity in 28 mNSCLC patients and possible changes in specific peripheral immuno-cell subsets, analyzed by flow-cytometry single cell bioinformatic approach. We recorded a treatment-related decline in the CD4+T, B cells and neutrophil to lymphocyte ratio, coupled with an increase of NKT, CD8+PD1+ T and eosinophils. Treatment-related increase in auto-antibodies as well as frequency of immune-related adverse events was also observed, and it was frequently associated with deregulation of specific immune subpopulations (e.g. NKT cells). Correlative biological/clinical studies with deep immune-monitoring are eagerly awaited to better characterize the effects produced by PD-1/PD-L1 immune-checkpoint blockade.